RECORDS OF TWO POTAMID FRESHWATER CRABS (DECAPODA: BRACHYURA) FROM GOMTI RIVER, UTTAR PRADESH - SAHU, ASHISH; SINGH, MAHENDER; SARKAR, UTTAM KUMAR (Journal of the Inland Fisheries Society of India, 2026)
Freshwater crabs are integral to aquatic habitats and play major roles in nutrient cycling and ecosystem functioning. However, their distribution and abundance in different river systems, including the Gomti River in Uttar Pradesh, remain poorly studied and documented. We collected crabs during the experimental sampling and identified them based on morphological characteristics. In the present study, we highlighted the occurrence of two potamid crabs, Acanthopotamon martensi (Wood-Mason, 1875) and Maydelliathelphusa masoniana (Henderson, 1893) from this ecosystem, which belongs to the Least Concern (LC) category as per IUCN Red List status. The study presents a preliminary investigation into the presence of freshwater crabs in the Gomti River. The measurements of A. martensi are 20.18 × 23.24 mm, while those of M. masoniana are 45.31 × 56.4 mm. Further studies are required to explore the species’ biology, taxonomy, major threats, and conservation needs, and to evaluate its potential for commercial fisheries. Future research could integrate molecular tools, such as DNA barcoding, alongside morphological data (integrative taxonomy), to enhance species identification and taxonomy. Environmental DNA (eDNA) technology could also be employed for more efficient detection and monitoring of freshwater crabs without capturing the individuals.